Antibiotic Resistance of Uropathogens Isolated from Patients Hospitalized in District Hospital in Central Poland in 2020 - Barbara Kot; Agata Grużewska; Piotr Szweda; Jolanta Wicha; Urszula Parulska (MDPI AG, 2021)
The aim of this study was to determine antibiotic resistance patterns and the prevalence of uropathogenes causing urinary tract infections (UTIs) in patients hospitalized in January-June 2020 in central Poland. Antimicrobial susceptibility testing was performed using the disk-diffusion method. Escherichia coli (52.2%), Klebsiella pneumoniae (13.7%), Enterococcus faecalis (9.3%), E. faecium (6.2%), and Proteus mirabilis (4,3%) were most commonly isolated from urine samples. E. coli was significantly more frequent in women (58.6%) (p = 0.0089) and in the age group 0-18, while K. pneumoniae was more frequent in men (24.4%) (p = 0.0119) and in individuals aged 40-60 and >60. Gram-negative species showed resistance to ampicillin. K. pneumoniae were resistant to amoxicillin plus clavulanic acid (75.0%), piperacillin plus tazobactam (76.2%), cefotaxime (76.2%), cefuroxime (81.0%), ciprofloxacin (81.0%), and trimethoprim plus sulphamethoxazole (81.0%). Carbapenems were effective against all E. coli and P. mirabilis. Some K. pneumoniae (13.6%) produced metallo-β-lactamases (MBLs). E. coli (22.6%), K. pneumoniae (81.8%), and all E. faecium were multidrug-resistant (MDR). Some E. coli (26.2%), K. pneumoniae (63.6%), and P. mirabilis (14.3%) isolates produced extended-spectrum beta-lactamases (ESBL). Vancomycin-resistant E. faecium was also found. This study showed that the possibilities of UTIs therapy using available antibiotics become limited due to the increasing number of antibiotic-resistant uropathogens.